Socioeconomic disparity in breast cancer detection in Hong Kong--a high income city: retrospective epidemiological study using the Breast Cancer Registry. - Josette Sin Yee Chor; Holly Ching Yu Lam; Amy Chan; Hang Mei Lee; Eliza Fok; Sian Griffiths; Polly Cheung (PLoS ONE)
Background It is not known whether socioeconomic disparities affect the detection of breast cancer in Asian countries where the incidence of breast cancer is a rising trend. In this study, we explore the socioeconomic profiles of women and the stage of the disease at the time of diagnosis in breast cancer patients aged 40 or over in Hong Kong. Method During the period 2008 to 2011, 5393 breast cancer patients registered with the Hong Kong Breast Cancer Registry. Participants and their clinicians were asked to complete standardised questionnaires including patient socio-demographics, health history and risk factors, the course of the disease, post-treatment physical discomfort and psychosocial impact, follow-up recurrence and survival status. Results Monthly household incomes, educational levels and the practice of regular screening are independently associated with the stage of the disease at diagnosis. Higher socioeconomic status and a higher educational level were associated with an earlier stage of the disease at the time of diagnosis. Yearly clinical examinations, ultrasound and mammographic screening every 2 to 3 years were significantly associated with the earlier detection of breast cancer. Conclusion There were socioeconomic disparities among Hong Kong women who were found to have breast cancer. Population-based screening policies, including raising awareness among women at risk, should be implemented.